The Effectiveness of Project-Based Learning in Enhancing Social Competence Among Elementary School Students - Rizal, Muhammad Syahrul; Murtadho, Nurul; Hanafi, Yusuf; Ananda, Rizki; Mufarizuddin, Mufarizuddin (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
Social skills are essential to 21st-century education, but many elementary school students in Indonesia still demonstrate low social skills due to the dominance of conventional teacher-centered learning approaches. This study aims to analyze the effect of Project-Based Learning (PjBL) on improving elementary school students' social skills and identify the dimensions of social skills that are most influenced by this approach. The study used a quasi-experimental design involving 80 fifth-grade students divided into an experimental group (PjBL) and a control group (conventional learning). The measurement instrument was a social skills test covering six dimensions: cooperation, communication, conflict resolution, empathy, decision-making, and leadership. Data analysis was conducted using t-tests after validity, reliability, normality, and homogeneity were confirmed. The results showed statistically significant differences (p < 0.05) between the two groups in all social skill dimensions, with the experimental group showing higher average scores. The dimensions of empathy and leadership showed the highest increases. These findings support social constructivist theory and strengthen the argument that collaborative, contextual learning can effectively develop students' social competencies. The implications of this study include the need for systematic adoption of PjBL in elementary schools as a strategy to support character-building and holistic learning in line with national curriculum requirements and 21st-century social needs.